2015
DOI: 10.3390/universe1020158
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Evaporation of Black Holes in Bigravity

Abstract: We review properties of solutions in bigravity theory for a specific case where two metric tensors, g µν and f µν , satisfy proportional relation f µν = C 2 g µν . For this condition, we find that the solutions describing the asymptotically de Sitter space-time can be obtained and investigate the perturbation around the Schwarzschild-de Sitter solutions and corresponding anti-evaporation. We discuss the stability under special perturbations related to the anti-evaporation and the importance of the non-diagonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
(61 reference statements)
2
11
0
Order By: Relevance
“…The existence of multi-horizon for massive gravity has been reported in Refs. [71,72] as well. It was shown that the existence of such property with specific quantum corrections leads to a phenomena which is opposite of the black holes evaporation.…”
Section: Black Hole Solutions In Massive Gravitymentioning
confidence: 98%
“…The existence of multi-horizon for massive gravity has been reported in Refs. [71,72] as well. It was shown that the existence of such property with specific quantum corrections leads to a phenomena which is opposite of the black holes evaporation.…”
Section: Black Hole Solutions In Massive Gravitymentioning
confidence: 98%
“…Antievaporation of Nariai black holes was found by Bousso and Hawking in quantum gravity coupled to a dilaton fields [39]. This phenomena was re-discovered by Nojiri and Odintsov in classical f (R)-gravity [40,41], and then in several different extension of general relativity [42,43,44,45]. As shown in Ref.…”
Section: T'hooft-polyakov Monopole and Bpst Instantonsmentioning
confidence: 74%
“…In addition to this it is also seen that massive gravity can alter the thermodynamic properties of black holes [19][20][21][22][23][24][25]. In particular, a behaviour similar to van der Waals' in the context of non-spherical black holes [26], Hawking temperature [27] and their anti-evaporation was also investigated [28,29]. Furthermore, massive gravitons in relation to gravitational waves during inflation has also been discussed [30].…”
Section: Introductionmentioning
confidence: 99%